Chemical speciation of MeHg+ and Hg2+ in aqueous solution and HEK cells nuclei by means of DNA interacting fluorogenic probes1. Issue 7 (15th July 2015) - Díaz de Greñu, Borja; García-Calvo, José; Cuevas, José; García-Herbosa, Gabriel; García, Begoña; Busto, Natalia; Ibeas, Saturnino; Torroba, Tomás; Torroba, Blanca; Herrera, Antonio; Pons, Sebastian
<x xml:space="preserve">Abstract</x> Speciation of Hg2+ and MeHg+ has been achieved by in vitro approaches with fluorogenic probes supported in cultured cells.